(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The objectives of this research were: 1) to study the current situation, problem, and need for Participative Supervision Model, 2) to develop the Participative Supervision Model, and 3) to try out and evaluate the application of Participative Supervision Model. There were 2 kinds of research instruments: the instrument using for work development, and the instrument using for data collection. The statistic consisted of the Percentage, Mean, and Standard Deviation. There were 3 Phases of implementation. Phase 1, the study of current situation, problem, and need for Participative Supervision Model, found that the problems needed to be developed most were: 1) the Students, 2) the Teachers, 3) the Administrators and Community, and 4) the Educational Supervision. Phase 2, the development of Participative Supervision Model consisted of 5 Steps of Participative Supervision Model including: 1) the Participative Planning, 2) the Participative Knowledge Construction, 3) the Participative Teamwork, 4) the Supervision Practice, and 5) the Participative Evaluation. Phase 3, the trying out and Evaluation of Application in Participative Supervision Model. The researcher tried out and evaluated all of 5 Steps and 10 activities of the Participative Supervision Model, in overall, the opinion was in “the Highest” level.